The component structure of teacher-musician's moral aesthetic activity (Pedagogy of Higher and Secondary Education, 2006)
In the article, the structure, the topical ness, and the criterions of the formed moral-aesthetic activity of teacher-musician are considered.
Keywords: moral-aesthetic activity; component structure; critenons